KEMAMPUAN KONEKSI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA BILANGAN BULAT DI SMP NEGERI 2 SUNGAI RAYA - Zulfa, Aini; Yusmin, Edy; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to describe student’s mathematical connection ability in solving word problems of integer at 7th grade of SMP Negeri 2 Sungai Raya. The research method was descriptive and research design was case study. The subject of this research was six students of 7th grade of class G. The subject was taken using test to know the basic ability of students. Based on the result of qualitative analitycal. There were three questions of word problems and each question had an indicator of mathematical connection. Students with high, medium, and low criteria can only complete two questions and no single student can complete the three test questions given. Based on the result of the research, it could describe the student’s mathematical connection ability in solving word problems of integer. Generally, students with high criteria could fulfill all of indicators of mathematical connection, students with medium criteria could fulfill two of three indicators of mathematical connection, and students with low criteria couldn’t fulfill any of indicators of mathematical connection. Keyword : Mathematical connection ability, Word problems, Integer